2021
DOI: 10.1053/j.gastro.2021.06.073
|View full text |Cite|
|
Sign up to set email alerts
|

Recurrent Frameshift Neoantigen Vaccine Elicits Protective Immunity With Reduced Tumor Burden and Improved Overall Survival in a Lynch Syndrome Mouse Model

Abstract: BACKGROUND & AIMS: DNA mismatch repair deficiency drives microsatellite instability (MSI). Cells with MSI accumulate numerous frameshift mutations. Frameshift mutations affecting cancer-related genes may promote tumorigenesis and, therefore, are shared among independently arising MSI tumors. Consequently, such recurrent frameshift mutations can give rise to shared immunogenic frameshift peptides (FSPs) that represent ideal candidates for a vaccine against MSI cancer. Pathogenic germline variants of mismatch re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 62 publications
2
56
0
Order By: Relevance
“…Remarkably, this group recently published a complementary study in mice models where they tested an FSP vaccine consisting of four shared FSP neoantigens derived from mouse coding mononucleotide repeats, which were in silico predicted and in vivo validated in naïve C57BL/6 mice. The vaccine effectively reduced intestinal tumor burden and prolonged overall survival in VCMsh2 mice, which have a conditional knockout of Msh2 in the intestinal tract and develop intestinal cancer [89]. Their findings prove that a recurrent FSP neoantigen vaccination for Lynch Syndrome cancer immunoprevention needs to be further evaluated.…”
Section: Tumor Specific Antigens and Neoantigensmentioning
confidence: 85%
“…Remarkably, this group recently published a complementary study in mice models where they tested an FSP vaccine consisting of four shared FSP neoantigens derived from mouse coding mononucleotide repeats, which were in silico predicted and in vivo validated in naïve C57BL/6 mice. The vaccine effectively reduced intestinal tumor burden and prolonged overall survival in VCMsh2 mice, which have a conditional knockout of Msh2 in the intestinal tract and develop intestinal cancer [89]. Their findings prove that a recurrent FSP neoantigen vaccination for Lynch Syndrome cancer immunoprevention needs to be further evaluated.…”
Section: Tumor Specific Antigens and Neoantigensmentioning
confidence: 85%
“…This is reminiscent of so called 'born to be bad' colon tumors that undergo a 'Big Bang' growth trajectory defined by the absence of selective sweeps 49 . Unlike models of familial cancer 47,48 , our models capture de novo loss of MMR in advanced tumors. Importantly, while Lynch syndrome accounts for less than 5% of CRC, about 10% of CRC harbors MMRd resulting from MLH1 promoter hypermethylation or other somatic events 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies employed tissue-specific knockout of Msh2 or activation of dominant proofreading mutant Pole (Pole P286R ) during embryogenesis to study the efficacy of prophylactic vaccination or ICB therapy on spontaneously arising hypermutant tumors in the mouse 47,48 . These models, which recapitulate familial cancers like Lynch syndrome in their accumulation of mutations in normal parenchyma preceding transformation, also showed response to immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike previous studies that demonstrated a role for MMRd and TMB in immunotherapy response, in which mutagenesis occurred in vitro 2,3,29 , our models enable study of mutations continuously acquired in vivo from tumor initiation through advanced disease. Other studies showed immunotherapy efficacy in autochthonous models of spontaneous cancer employing tissue-specific knockout of Msh2 or activation of mutant Pole (Pole P286R ) during embryogenesis 40,41 . These models recapitulate familial cancers like Lynch syndrome in the accumulation of mutations in normal parenchyma preceding transformation (<5% of CRC), but not sporadic loss of MMR in established tumors (~10-15% of CRC) 15,16 .…”
Section: Discussionmentioning
confidence: 99%